Some Teratogenic Outcomes in Rats Exposed to Zinc Chloride Pre and Post Pregnancy - Zaher, Abdul-Rahman; AL-Rekabi, Falah M; Akram Hatif, Saad (The Iraqi Journal of Veterinary Medicine, 2021)
The aim of present study was to evaluate the possibility of teratogenicity in rats when exposed to zinc chloride (ZnCl2) pre and post pregnancy. To achieve this goal, a total of 40 mature Albino Wistar female rats were divided equally into four groups as follows: T1, dosed 0.7 mg/day ZnCl2 for two months before mating and till to the day 5th of pregnancy, the females of this group were mated with males dosed 0.7 mg/day ZnCl2 for two weeks before mating; T2, dosed 0.7 mg/day ZnCl2 for two months before mating and till to the day 16th of pregnancy and then were mated with control males (not exposed to any level of ZnCl2); T3, dosed 0.7mg/day ZnCl2 for two months before mating and till the end of pregnancy and were mated with control males; Control, dosed with water free from ZnCl2 along the period of experiment and were mated with control males. At the end of each pregnancy phase, results revealed that alpha fetoprotein serum levels were significantly (P<0.05) higher in all treatment groups compared to the control group, and the most prominent increase was observed in the T3 group. All treatment groups showed a significant (P<0.05) decrease in gestation, viability, and lactation indices when compared to the control group, with the T3 group showing the most significant decrease. Additionally, on days 1, 4, 7, 14, and 21 of lactation period, there was a significant (P<0.05) decrease in mean pup body weights in treated groups compared to the control group, with T3 group having the most prominent body weight decrease. The findings of this study revealed that ZnCl2 at a daily dose of 0.7 mg may cause teratogenic defects in rats at various stages of pregnancy, particularly at the third stage. As high-risk groups, pregnant women and children should use Zn supplementation carefully, whether as a food additive or for self-medication. Simultaneously, evaluating effect of low-dose Zn supplementation over a longer duration is required.